Round baled grass silage as food for reindeer in winter - Aagnes, Tove H.; Mathiesen, Svein D. (Rangifer, 1995)
Round baled silage of mixed grasses was tested as emergency food for reindeer in winter. The silage was made of leaf rich regrowth of Phleum pratense, Agrostis tenuis and Poa spp. It contained 33-3% dry matter (DM), and 14.8 % crude protein, 24.5% cellulose and 26.7% hemicellulose on a DM basis. Palatability, food intake, digestion, rumen fermentation, body mass (BM), carcass weight and gastrointestinal (GI) anatomy were investigated. A group of adult female reindeer (n = 38), were taken from natural winter pasture and fed grass silage ad libitum. The majority (78%) of the animals were eating silage after two days and 95% of the animals ate silage after five days. Five reindeer calves were taken from natural winter pasture and fed lichens ad libitum for 14 days after which they were starved for two days before being offered silage adlibitum. The median daily DM food intake was 370 g (range 250-610 g) on the first day increasing to 810 g (range 530-1100 g) at days 16 to 20. Median apparent digestibility coefficient (DC) of DM was 64.3% (range 62.4-66.2%). The median in vitro DM digestibility (IVDMD) of the silage after 72 h of microbial digestion was 68.3 % (range 66.6-71.3 %) (Ws=30, n,=5, n2=4, P<0.01). Median ruminal VFA concentration and pH were 48.2 mM (range 38.4-52.5 mM) and 7.0 (range 6.95-7.17), respectively, in the reindeer calves (n=5). BM initially increased when the reindeer calves were fed silage, but stabilised after 11 days. The increased BM may have been due to an increased recticulo-rumen digesta load, which amounted to 19.6-23.7 % of BM (n=3). The carcass weight of the reindeer calves was 42.6-44.2% of the BM (n=3) after 47 days of silage feeding. The results indicate that although the round bale silage of mixed grasses of medium quality was highly palatable to reindeer it was apparantly of only limited value as an emergency food for the reindeer calves, as indicated by low DC of DM and low ruminal VFA concentration.